Investigation of the Effect of SCAMPER Technique on Eighth Grade Students' Academic Achievement, Environmental Attitudes and Science Learning Motivations - Polat, Mehmet; Yilayaz, Ömer (Ozgen Korkmaz, 2026)
The SCAMPER technique, one of the creative thinking technique, focuses on developing creative and innovative solutions by systematically reviewing possible changes that can be made on a situation or problem. In this study, the effect of SCAMPER technique on eighth grade students' academic achievement, environmental attitudes and motivation to learn science in the unit “Sustainable Life and Material Cycles (SLMC)” was examined. This study, which was conducted with 59 eighth grade students studying in a public secondary school in the Eastern Anatolia Region in the 2022-2023 academic year, was designed according to a pretest (PrT)-posttest (PsT) control group experimental design. The data of the study were collected through the “Sustainable Living and Material Cycles Academic Achievement Test” (SLMCAT), “Environmental Attitude Scale” (EAS) and “Science Learning Motivation Scale” (SLM). The study first conducted descriptive analyses, and the results showed that the increase in EGR's SLMCAT, EAS, and SLM final test scores was significantly higher than that of CGR. MANCOVA findings also supported this result; it was revealed that the SCAMPER technique had a statistically significant and high-level effect on SLMCAT, EAS and SLM PsT scores (SLMCAT: ?2 = .801, EAS: ?2 = .841, SLM: ?2 = .750). In the CGR, no significant change was observed in the PsT scores. These result show that SCAMPER technique can create more effective learning environments in teaching abstract and complex subjects. It was also concluded that this approach has a significant potential in improving students' attitudes towards the environment and increasing their motivation towards science learning. © 2026, Ozgen Korkmaz. All rights reserved.
Keywords: creative thinking; SCAMPER; science education